Pelatihan Karyawan Terkait Product Knowledge Pada PT Topindo Atlas Asia (Top 1 Oil) - Lestari, Naida Fadilah; Supardi, Supardi (JURNAL MAHASISWA BINA INSANI; Vol 7 No 2 (2023): Jurnal Mahasiswa Bina Insani (Februari 2023), 2023)
The research is motivated by a major challenge for companies to create competent employees and thus be able to help company compete in the big market. The purpose of this research is to know employee knowledge regarding products. This research method uses primary and secondary types of data, data-collecting techniques with interviews, observation, and documentation, while the research analysis techniques used are qualitative. The analysis showed that PT Topindo Atlas Asia (Top 1 Oil) has implemented most of the concepts of good training, but there is still room for more in the frequency of training. The problem with this research is employee knowledge regarding the Top 1 product is not maximum. The solution given regarding the problem is to produce a product card so that the employee knowledge of the product increases and thus be able to make it easier for them to promote and sell products.